STATUS KESEHATAN MASYARAKAT DAN KUALITAS LINGKUNGAN PADA DAS GARANG KABUPATEN DAN KOTA SEMARANG (Studi Analisis Spasial Pada daerah Urban, Rural, Pantai, Pegunungan) - Sulistiyani - (Universitas Muhammadiyah Semarang, 2004)
Program need information and data for planning, evaluation and monitoring. But much data never to do analysis, example service based data from Health Center. The aim of this research is to know public health statue and environment quality at DAS Garang in Semarang City and Regency with spasial analysis from urban, rurel, seashore,mountain range. The Results of this research show that dominant factor of environment is water especially microbiologt. Health Statuei in Urban that is ARI, Diarrhea, Dysentry, Skin and Eye for group of>60 years. In Rural far group of 0-4 years old : ARI, Diarrheo, Skin and Eye. In seashore area ARI, Skin and Eye for group of >60 years.ln Mountain ronge is ARI, Diarrhea, Skin and Eye for group of 0- 4 years old.